Gender implications of climate change for an eco-efficient agriculture - Gómez, Juliana (International Center for Tropical Agriculture, 2009)
The PRGA Program has launched a new initiative focused on mitigation efforts to adapt breeding techniques to the effects of Climate Change. These efforts are carried out in partnerships with ICARDA and stakeholder organizations in various regions.